Effect of Saline Water Irrigation and Dilution of Salts on Water Management Water in Green Pepper - Muhammad Arshad; Muhammad Kaleem Ullah; Asad Iqbal; Muhammad Usman Tariq; Ahmad Waqas (Pakistan Journal of Engineering & Technology, 2021)
Irrigation has an important role in food production worldwide by increasing crop quality and production. As such, the use of fresh water for agricultural or vegetable products is declining in quantity and quality over the coming decades. A major factor in brine water is abiotic stress, which disrupts efficiency and is one of the major sources of significant crop loss worldwide. The vegetable is the most commonly cultivated vegetable crop in Pakistan, which has wide economic potential, but its productivity and quality, diseases, nutritional deficiencies, and insect pests or stresses include cold, heat, salinity, drought, and mild stress. The main objective of this research is to observe the effect of saltwater irrigation on green paper. Assessment of various salt-water regimes in terms of their impact on plant growth. Detection of salinity levels and salt-water regimes. The research was conducted at the Water Management Research Center Agricultural University, Faisalabad. Experimental Station of the Water Management Research Center in the Punjab (Pakistan) Province during the spring and summer of 2019. The results of this study confirm the utility of salt variation in pepper plants. Plants were classified as salt-tolerant and sensitive based on the parameters studied. NaCl nutrient solutions of less than 2 (g) have been shown to tolerate excess salt in all plants, and other plants have proven to be highly salt-sensitive at all salinity levels. Salinity is the major stressor in all of these stresses due to the lack of drainage water or groundwater used for sewage for irrigation. For every part of the salinity level beyond its limit, the yield of pepper decreases by 14%.